Polysaccharide-based responsive hydrogels for nerve regeneration - Mittal P.; Chopra H.; Kapoor R.; Mishra B. (My University, 2025)
Self-healing 3D bioresponsive hydrogels are excellent for the treatment of neurological diseases as well as for the regeneration of neurons. Neural stem cell (NSC) transplantation therapy is the best alternative to treat neurological disorders. When NSCs are incorporated into 3D hydrogels and inserted in the brain tissue, they start growing in naturally. Regenerating hydrogels possess advantages such as preventing cellular loss and shock to the cells due to the shear stress caused by the needle during the injection administration. Soft and regenerative hydrogels containing NSCs possess a 3D extracellular structure similar to that of soft tissues. Injectable 3D hydrogels can deliver the cells to their microenvironments without any local lesions. However, the formulation of biocompatible smart self-healing and regenerative hydrogels with embedded delicate NSCs into them is somewhat challenging. This chapter will provide a detailed review of the properties, manufacturing, and self-healing aspects of 3D gels. © 2024 Elsevier Inc. All rights reserved.